Partisipasi Stakeholders dalam Pembinaan Anak Berhadapan Hukum di Lembaga Kesejahteraan Sosial Ummu Syahidah Provinsi Gorontalo - Najamuddin Petta Solong; Ahmad Fakhrurrazi Mohammed Zabidi; Yuslin Kasan; Ni’ma M Alhabsyi (Al-Ulum, 2022)
This study aims to analyze stakeholder participation in the development of children against the law. This research method is descriptive qualitative because it has a natural background, researchers are key tools (instruments), data analysis is carried out inductively, and grounded theory and descriptive. The approach used is phenomenological. The findings in this study prove that the participation applied by stakeholders is adjusted to the activities of social workers including: (a) participation related to administration and documentation, (b) identification and assessment process, (c) fulfillment of basic rights, guidance and guidance, (d) referral and reunification services, and (e) participation in post-return monitoring and reunification.